2006
DOI: 10.1128/jvi.02615-05
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Type 1 Latently Infected Neurons Differentially Express Latency-Associated and ICP0 Transcripts

Abstract: Herpes simplex virus type 1 (HSV-1) is a human neurotropic virus, which establishes lifelong latent infection. During the acute phase of infection, viral replication is characterized by the expression of immediate early (IE), early, and late genes in an ordered cascade that leads to the release of infectious particles that can attach to nerve endings. Following axonal transport to neuronal cell bodies, HSV-1 can either replicate or persist in a latent state in the infected host (62).During latency infectious v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 81 publications
5
46
1
Order By: Relevance
“…We subsequently conducted immunofluorescence staining with ICP0 monoclonal antibodies, but did not detect any ICP0 protein in acutely infected TGs either in mice or in tree shrews (data not shown). This result is supported by the earlier study of Chen et al, in which they observed ICP0 transcripts but no ICP0 protein in primary neuron cultures (39) and the studies of Mailett et al, who studied ICP0 expression in an oro-ocular model of HSV infection and noted ICP0 transcripts in the nuclei of some neuronal cells during latency (38). The level of ICP0 transcript will be further investigated later in this study.…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…We subsequently conducted immunofluorescence staining with ICP0 monoclonal antibodies, but did not detect any ICP0 protein in acutely infected TGs either in mice or in tree shrews (data not shown). This result is supported by the earlier study of Chen et al, in which they observed ICP0 transcripts but no ICP0 protein in primary neuron cultures (39) and the studies of Mailett et al, who studied ICP0 expression in an oro-ocular model of HSV infection and noted ICP0 transcripts in the nuclei of some neuronal cells during latency (38). The level of ICP0 transcript will be further investigated later in this study.…”
Section: Resultssupporting
confidence: 77%
“…8H). Although we could hardly detect ICP0 transcript in mouse latently infected TGs, ICP0 transcript has been detected during latency in mice by others (38); nonetheless, both in situ hybridization results discussed here and qRT-PCR results shown in Fig. 6 strongly suggest that latently infected tree shrew TGs express much higher levels of ICP0 transcript than mouse TGs during HSV-1 latency.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Evidence that expression of LATs and expression of ICP0 gene may be incompatible was reported by Amelio et al (16) and Maillet et al (17). The studies with actinomycin D and cycloheximide suggest that these two events are linked.…”
Section: Discussionmentioning
confidence: 72%
“…The exogenous expression of ICP0 or pp71 can activate gene expression from quiescent HSV-1 genomes [98][99][100][101]. Furthermore, latently-infected cells express antisense transcripts that may affect the expression of ICP0 [102][103][104][105] or pp71 [106], implying that repressing the expression of these proteins may be important for the maintenance of the latent state. For HSV-1, chromatin remodeling to achieve or maintain viral genome silencing also seems to occur through additional processes independent of PML-NB proteins [107].…”
Section: While They Inhibit Lytic Replication Do Pml-nb Proteins Facmentioning
confidence: 99%